Pengaruh Kepercayaan, Kemudahan Dan Kualitas Informasi Terhadap Keputusan Pembelian Pada Marketplace Shopee - Ila Jannatil Makwa; Muhammad Ridwan Basalamah; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the relationship between the variables of trust, ease and quality of information on purchasing decisions at the shopee marketplace. This research is a quantitative research. The data collection method in this study used a questionnaire with a total sample of 90 respondents. The data analysis method used in this research is using multiple linear regression analysis. Method. Based on the results of this study that trust, ease and quality of information simultaneously affect purchasing decisions Keywords : Trust, Convenience, Quality Of Information And Purchasing Decisions